Activities and Institutional Mechanism of MNREGA and its Effectiveness in West Bengal - Shubhadeep Roy , Baldeo Singh , R.N. Padaria and Neeraj Singh, (Indian Journal of Extension Education, 2014)
The study was conducted in two districts, Burdwan and South Dinajpur of West Bengal with 200 Mahatma Gandhi National Rural Employment Guarantee Act (MNREGA) beneficiaries as respondents to assess the perceived effectiveness of MNREGA and to understand different activities and institutional mechanisms involved in MNREGA. The results revealed that rural connectivity was the most preferred work under the programme. Works like land development and renovation of traditional water bodies were benefiting local agriculture. A conceptual model of institutional mechanism of MNREGAfunctioning has been proposed which implies, inclusion of educational institutions in MNREGAwhich may enhance the quality of the programme and the beneficiaries may be benefitted. More than 50 per cent of the respondents perceived that MNREGAwas functioning effectively at the grass root level.